Seasonal variability of copepod community structure and abundance modified by the El Niño-La Niña transition (2010), Pacific, Mexico - Kozak, Eva R.; Olivos-Ortiz, Aramis; Franco-Gordo, Carmen; Pelayo-Martínez, Gloria (Revista de Biología Tropical, 2018)
Copepods are an important planktonic group, and account for most of the total biomass and species diversity in pelagic marine ecosystems. Seasonal variability of the community structure of copepods in the Eastern tropical Pacific off central Mexico was studied during three distinct hydrodynamic periods in 2010 using statistical and multivariate analyses. The survey period included the second half of the 2009-2010 El Niño (January), the neutral transition period (May-June), and the first half of the 2010-2011 La Niña (October). Seventy-eight copepod species were identified; richness ranged from 11 to 47 species per station, with seasonal averages from 25 species in May to 35 species in January. Cluster analysis indicated that there were four principal groups present across the surveyed periods, defined by January (El Niño), October (La Niña), May offshore stations, and May upwelling stations (cyclonic eddy and coastal stations). There were no significant differences in abundance, but the January (El Niño) cluster was most diverse with 32 species, May offshore and October (La Niña) clusters each had 25 species, and the May upwelling was the least diverse cluster with 18 species. Mesoscale processes were strongest during May, which was the only period with a significant inshore-offshore gradient of species richness and diversity. Canonical correspondence analysis (CCA) revealed that variability was primarily driven by subsurface (75-200 m) ammonium, and surface (0-50 m) temperature, nitrates+nitrites, salinity and phosphorus. Copepodites and adults of the primarily herbivorous Eucalanidae dominated the stations of the upwelling cluster, while copepodites and adults of the carnivorous Euchaetidae dominated the January (El Niño) station cluster. The higher Chl a levels during the less productive (reduced upwelling) El Niño period were probably due to reduced grazing activities and increased ammonium availability through increased zooplankton metabolism. The horizontal distribution of copepods in the Eastern Tropical Pacific off Mexico appears to be principally defined by mesoscale eddy processes (offshore) and upwelling (coastal). These mesoscale processes were affected by El Niño - La Niña transitions, which subsequently disrupted the inshore-offshore gradient and in the case of El Niño likely caused reductions in copepod abundance across the entire region which persisted for the entire study period, and possibly longer.